History of Formation of Religious Science - Dilafruz Mahmudjanovna Turdieva (Researchparks Publishing, 2022)
Because of independence, our country has had an opportunity to look at and state the attitude on religion in a new way. As a result, the science of theology, which is relatively new to us, emerged. This science aims not to criticize or remove religion from society, but to study it objectively, looking at religion as part of the national spirituality. The science of religion was formed and developed in close connection with the social sciences and humanities, and this process is still going on. Accordingly, in the place where the science of religion is intertwined with these sciences, its various branches have emerged. The current article gives various definitions of the term religion, the formation of theology as a science, and the scholars who have made a worthy contribution to it.